The Effect of Irrigation on the Yield and Soybean (Glycine max L. Merr.) seed Germination in the Three Climatically Varying Years - Dari Galić Subašić; Irena Rapčan; Malden Jurišić; Davor Petrović; Dorijan Radočaj (Poljoprivreda)
The paper presents the results of a three-year investigation of the effect of irrigation on the germination and yield of soybeans in three climatically different years in the conditions of eastern Croatia. The experiment was conducted with four soybean varieties (Lucija, Tena, Ika, and Vita) of different maturity groups and in different irrigation treatments (control: natural conditions, rational: 60–100% soil-water retention capacity (SWRC), and abundant irrigation: 80–100% SWRC). An analysis of variance revealed a statistically significant effect of irrigation on the yield throug-hout all three study years. The variety selection affected the yield in 2013 and 2014, while it did not manifest a statistical significance in 2015. The effect of irrigation on seed germination was exerted only in 2015, and an interaction between the irri-gation and soybean variety was not observed in any of the study years. According to the results of the LSD0.05 test, statistically significant differences were observed between the irrigation methods, whereby the t largest statistical difference in. seed germination was achieved with abundant irrigation (LSD0.05 = 1.2039). A correlati-on analysis between the yield and germination produced a statistically significant positive correlation, which was weaker in 2013 and 2014, it was more pronounced in 2015 (r = 0.427*).